2021
DOI: 10.1016/j.dib.2021.107182
|View full text |Cite
|
Sign up to set email alerts
|

Emotion regulation, psychological distress and demographic characteristics from an Ecuadorian sample: Data from the lockdown due to COVID-19

Abstract: Due to the rapid spread of COVID-19, several governments around the world implemented strict lockdown measures. However, these measures produced a number of negative psychological effects, such as increased anxiety and depression [1 , 2] . This article presents raw data from variables related to psychological distress, and from possible sources of psychological distress, such as the use of certain emotion regulation strategies, exposure to different media sources, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 7 publications
0
2
0
3
Order By: Relevance
“…No compensation was offered for participation. More detailed information about the sample can be found in Rodas et al ( 2021 ). According to two power analyses conducted with G*Power (Faul et al, 2009 ), the number of participants used for the multiple regression models (for anxiety and depression) provided 100% power in both models according to the effect sizes found in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…No compensation was offered for participation. More detailed information about the sample can be found in Rodas et al ( 2021 ). According to two power analyses conducted with G*Power (Faul et al, 2009 ), the number of participants used for the multiple regression models (for anxiety and depression) provided 100% power in both models according to the effect sizes found in our analyses.…”
Section: Methodsmentioning
confidence: 99%
“…La primera muestra corresponde a participantes durante los primeros meses de la pandemia en Ecuador, una situación de gran temor por la salud y de la implementación de estrictas medidas de bioseguridad. Esta población ha demostrado reportar niveles de ansiedad y depresión clínicamente considerables (Rodas et al, 2021(Rodas et al, , 2022. La segunda muestra corresponde a apostadores, tanto habituales como con problemas de juego que se encuentran internados por tratamiento a problemas de adicción.…”
Section: Tablaunclassified
“…No se ofreció ningún tipo de compensación por participar. En Rodas et al (2021Rodas et al ( , 2022 se encuentra información más detallada de la muestra en la que se incluyen a participantes de diversos países de América y Europa. Para este estudio, solo se utilizó el segmento de la muestra conformado por ecuatorianos.…”
Section: Estudio 1 Participantesunclassified
See 1 more Smart Citation
“…During the time of assessment, 381 participants had a job, however, 433 indicated that they had enough savings for the lockdown. More detailed EMOTION REGULATION DURING LOCKDOWN information from the sample can be found in Rodas et al (2021). According to two power analyses conducted with G*Power (Faul et al, 2009), the number of participants used for the multiple regression models (for anxiety and depression) allowed to achieve 100% power in both models, according to the effect sizes obtained from the R 2 of each model (f 2 = .616 for depression; f 2 = .35 for depression).…”
Section: Participantsmentioning
confidence: 99%